Asian Military Evolutions Civil-Military Relations in Asia (Bristol University Press, 2023)
This book explores civil-military relations in Asia. With chapters on individual countries in the region, it provides a comprehensive account of the range of contemporary Asian practices under conditions of abridged democracy, soft authoritarianism or complete totalitarianism. Through its analysis, the book argues that civil-military relations in Asia ought to be examined under the concept of 'Asian military evolutions.' It demonstrates that while Asian militaries have tried to incorporate standard, western-derived frameworks of civil-military relations, it has been necessary to adapt such frameworks to suit local circumstances. The book reveals how this has in turn led to creative fusions and novel changes in making civil-military relations an asset to furthering national security objectives